Blood pressure–lowering efficacy of indapamide SR/amlodipine combination in older patients with hypertension: A post hoc analysis of the NESTOR trial (Natrilix SR vs Enalapril in Hypertensive Type 2 Diabetics With Microalbuminuria). Issue 10 (18th July 2017) - Hanon, Olivier; Caillard, Laure; Chaussade, Edouard; Hernandorena, Intza; Boully, Clemence
Abstract : To examine the antihypertensive efficacy and safety of indapamide sustained‐release (SR)/amlodipine compared with enalapril/amlodipine in patients 65 years and older with uncontrolled blood pressure (BP) on monotherapy, a post hoc analysis of the NESTOR trial (Natrilix SR vs Enalapril in Hypertensive Type 2 Diabetics With Microalbuminuria) was conducted. NESTOR randomized 570 patients (n=197, aged ≥65 years) with hypertension (systolic BP 140–180/diastolic BP <110 mm Hg) to indapamide SR 1.5 mg or enalapril 10 mg. If target BP (<140/85 mm Hg) was not achieved at 6 weeks, amlodipine 5 mg was added with uptitration to 10 mg if required. A total of 107 patients aged 65 years and older received dual therapy (53 indapamide SR/amlodipine and 54 enalapril/amlodipine). Amlodipine uptitration occurred in 22 and 24 patients, respectively. At 52 weeks, mean systolic BP (±SE) reduction was significantly greater with indapamide SR/amlodipine vs enalapril/amlodipine 6.2±2.7 mm Hg ( P =.02). Indapamide SR/amlodipine was also associated with a greater BP response rate (88% vs 75%, respectively). Both regimens were well tolerated. Indapamide SR/amlodipine may be more effective than enalapril/amlodipine for lowering systolic BP in patients with hypertension aged 65 years and older.